DIAGNOSTIC EFFICACY OF RED BLOOD CELL INDICES IN DIAGNOSIS OF BETA THALASSEMIA TRAIT TAKING HAEMOGLOBIN ELECTROPHORESIS AS GOLD STANDARD - Rabbani, Sahar; Farooq, Muhammad; Naeem, Samina; Uddin, Nasir; Naeem, Muhammad Abdul; Jabeen, Shahneela (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the diagnostic efficacy of haematological indices for the diagnosis of beta thalassemia trait taking haemoglobin electrophoresis as a gold standard. Study Design: Cross sectional study. Place and Duration of Study: Department of Haematology Combined Military Hospital Lahore, from Aug to Dec 2019. Methodology: Two hundred and six anaemic patients 20-70 years of age of both genders were included in the study. Blood was collected from all the patients and complete blood count were generated through automated haematology analyser Sysmex KX-21. Based on the complete blood count parameters like mean cell volume, red blood cell count, red cell distribution width and mean cell haemoglobinthe haematological indices such as Mentzer, Ricerca, mean density of Hb/litre of blood, mean cell Hb density and red cell distributon width indices were calculated. The haemoglobin A2 band of >3.5% on haemoglobin electrophoresis was taken as cut off for Beta thalassemia trait. Results: Out of the 206 blood samples analysed, 120 (58%) were labelled as Beta thalassemia trait after Hb electrophoresis and 86 cases had anemia due to other causes. Mentzer index established the highest sensitivity of 92.5% whereas RICERCA index established the highest specificity of 94.1%. Mentzer and red cell distribution width indexhad highest diagnostic efficacy value up to 90.3%. Conclusion: We conclude that Mentzer and red cell distribution width index showed the highest diagnostic significance. The Mentzer index has the highest sensitivity whereas Ricerca index has the highest specificity. The red blood cell count, haemoglobin and mean cell volume.............